18‐3: Free Viewpoint Teleconferencing Using Cameras Behind Screen. Issue 1 (28th June 2021) - Lim, Sehoon; Liang, Luming; Zhong, Yatao; Emerton, Neil; Large, Tim; Bathiche, Steven
Abstract : Natural interaction in videoconferences can be made by correcting gaze/perspective, scale, and position by using cameras placed behind a partially transparent front emitting OLED panel and frame interpolation of deep neural networks. The diffraction artifacts from through‐screen imaging are removed by a deconvolution method.